Modulation of HIV-1 capsid multimerization by sennoside A and sennoside B via interaction with the NTD/CTD interface in capsid hexamer - Zhang, Da-Wei; Xu, Xiao-Shuang; Zhou, Rui; Fu, Zhiguo (Frontiers in Microbiology, 2023)
Small molecules that bind to the pocket targeted by a peptide, termed capsid assembly inhibitor (CAI), have shown antiviral effects with unique mechanisms of action. We report the discovery of two natural compounds, sennoside A (SA) and sennoside B (SB), derived from medicinal plants that bind to this pocket in the C-terminal domain of capsid (CA CTD). Both SA and SB were identified via a drug-screening campaign that utilized a time-resolved fluorescence resonance energy transfer assay. They inhibited the HIV-1 CA CTD/CAI interaction at sub-micromolar concentrations of 0.18 μM and 0.08 μM respectively. Mutation of key residues (including Tyr 169, Leu 211, Asn 183, and Glu 187) in the CA CTD decreased their binding affinity to the CA monomer, from 1.35-fold to 4.17-fold. Furthermore, both compounds induced CA assembly in vitro and bound directly to the CA hexamer, suggesting that they interact with CA beyond the CA CTD. Molecular docking showed that both compounds were bound to the N-terminal domain (NTD)/CTD interface between adjacent protomers within the CA hexamer. SA established a hydrogenbonding network with residues N57, V59, Q63, K70, and N74 of CA1-NTD and Q179 of CA2-CTD. SB formed hydrogen bonds with the N53, N70, and N74 residues of CA1-NTD, and the A177and Q179 residues of CA2-CTD. Both compounds, acting as glue, can bring αH4 in the NTD and αH9 in the CTD of the NTD/CTD interface close to each other. Collectively, our research indicates that SA and SB, which enhance CA assembly, could serve as novel chemical tools to identify agents that modulate HIV-1 CA assembly. These natural compounds may potentially lead to the development of new antiviral therapies with unique mechanisms of action.